Mass Gatherings Egress Vulnerability - Lenard Cheng; Cara Taubman; Marc-Antoine Pigeon; Ryan Hata; Derrick Tin; Gregory Ciottone (Universitas Gadjah Mada, 2025)
In this short letter, we discuss the concept of egress from mass gatherings as an unrecognised area of vulnerability in planning and disaster risk reduction. Current approaches isolate egress as a physical exit, and dichotomise the venue exit from transportation away from mass gatherings. We discuss historical mass gatherings disasters that have been contributed by this flawed approach to planning. Instead, we propose that venue exit and outbound transport be considered a singular process during planning, and suggest novel mass gatherings planning strategy for egress to reduce risk of disasters.